Islandborn - d uthor; Espinosa, Leo (New York, NY : Dial Books for Young Readers, 2018)
"Lola was just a baby when her family left the Island, so when she has to draw it for a school assignment, she asks her family, friends, and neighbors about their memories of her homeland ... and in the process, comes up with a new way of understanding her own heritage"--
Elementary Grade.
600
Accelerated Reader
Accelerated Reader AR
Keywords: Islands -- Juvenile fiction; Dominican Americans -- Juvenile fiction; Schools -- Juvenile fiction; Immigrants -- Juvenile fiction; Islands -- Fiction; Dominican Americans -- Fiction; Islands -- Fiction; Dominican Americans -- Fiction; Schools -- Fiction; Immigrants -- Fiction; JUVENILE FICTION -- Family -- Multigenerational; Dominican Americans; JUVENILE FICTION -- People & Places -- Caribbean & Latin America; JUVENILE FICTION -- People & Places -- United States -- Hispanic & Latino; JUVENILE FICTION -- Family -- Multigenerational; Dominican Americans; Emigration and immigration; 1930-1961; Juvenile works; Picture books; Sophisticated picture books; Fiction